Investigations on tailoring physical properties of RF magnetron sputtered Cadmium Sulphide thin films - Trivedi, Harshita; Ghorannevis, Zohreh; Chaudhary, Shilpi; Parmar, Avanish S. (Elsevier B.V., 2023)
The effect of nitrogen (N2) partial pressure on the structure and bandgap tunability of RF magnetron sputtered Cadmium Sulphide (CdS) thin films is investigated by varying N2 partial pressure in Ar/N2 mixture. In presence of N2, films have a polycrystalline structure with (0 0 2) preferential orientation, which leads to defect-free, continuous, dense, and fibrous structures with increased roughness. The average optical transmittance increased to > 80 at 500–2500 nm for 30 % N2 partial pressure, whereas the band gap decreases from 2.45 eV to 2.30 eV with increasing N2 concentration. This work shows that the bandgap of sputtered CdS thin films can be tuned with the variation of N2 concentration for customized applications.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: CdS; N2 concentration; Optical properties; RF sputtering; Thin-films